Analisis Rancangan Perencanaan Biaya dengan Metode Perhitungan Biaya Nyata Pada Pelaksanaan Proyek Perumahan Sederhana - Ella Anastasya Sinambela; Muhammad Djaelani (Journal of Trends Economics and Accounting Research, 2021)
Construction implementation has a variety of activities. Starting from the construction site survey activities. Building design planning, cost planning, building materials needed, planning the number of workers used, the construction process, and the final work. Therefore construction activities require construction management. Construction management is carried out according to the budget plan made so that an important activity in construction is the budget plan. This study aims to determine cost budgeting by using real cost calculations on house construction projects. The research was conducted at the Mentari Bumi Sejahtera housing complex, Candi Sidoarjo, East Java. This research shows that the actual cost budget is Rp. 285,883,236.51. Furthermore, the costs incurred when carrying out construction to completion are Rp. 259,523,836.51. Thus, the construction activities in this study earned a profit of Rp. 26,359,400